A Modulation Scheme for Floating Source Multilevel Inverter Topology with Increased Number of Output Levels - Hussain M. Bassi (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presented and studied a new switching scheme for floating source multilevel inverters to produce more levels with the same number of switching devices. In the proposed scheme, the function of the dc sources, except the inner one, is to build up square wave or blocks that is close in the shape to the desired sinusoidal wave. The job of the inner switching devices is to increase the number of the levels to produce smother sinusoidal wave in the inverter output. This job can be done by adding or subtracting the value of the inner dc source to/from the blocks. The topology used in this paper is based on the conventional floating source multi-level inverter using two legs. This topology and modulation technique show substantial reduction in the total harmonics distortion when the modulation technique is the hybrid method. The performance of the proposed switching scheme in generating more levels has been evaluated by PSCAD/EMTDC simulation.